Industry Competitiveness Indicators - Mette Asmild; Tomas Baležentis; Jens Leth Hougaard (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2019)
It can be argued that the competitiveness of an industry consists of two main parts: The production conditions and the utilization of these. The production conditions are largely determined by factors exogenous to the firms comprising the industry, including the economic environment, regulatory framework, etc. The utilization of the production conditions corresponds to the classic economic notion of structural efficiency. We here argue that it is crucial for policy analysis to be able to quantify each of these two aspects separately, since the production conditions are partly in the hands of the policy makers, whereas the utilization is mainly the responsibility of firm management. In this paper we define two new bilateral indicators; the Bilateral Industry Utilization (BIU) indicator, and the Bilateral Production Conditions (BPC) indicator. These are applied to a large data set of dairy farms across 19 European countries provided by the Farm Accountancy Data Network (FADN). With focus on the competitiveness of Danish dairy farms we show that dairy farms in most other countries have significantly better production conditions than those in Denmark while Sweden is the only country with significantly better utilization. Finally, we asses potential causes behind the differences and discuss possible remedies.
Keywords: C61; D04; E23; O47; Q12; 330; Competitiveness indicators; Production conditions; Structural efficiency; Bilateral indicators; Dairy farms; Efficiency; Frontier analysis; Jackknifing